Faktor Penyebab Dan Upaya Penanggulangan Tindakan Main Hakim Sendiri (Eigenrichting) Di Kota Kupang - Panduwal, Bryan; Leo, Rudepel Petrus; Manuain, Orpa G (Law Faculty, Nusa Cendana University, 2025)
The main problems in this thesis are: (1) What are the factors that cause society to tend to take the law into their own hands (eigenrichting) in crime cases that occur in Kupang City? (2) What countermeasures are made so that society does not take the law into their own hands (eigenrichting) in crime cases that occur in Kupang City? The results of this study is: (1) There are six factors that cause people to tend to take the law into their own hands (eigenrichting) in criminal cases that occur in Kupang City. (2) Efforts made to prevent people from taking the law into their own hands (eigenrichting) in criminal cases that occur in Kupang City are: (a) Preemptive efforts, (b) preventive efforts and (c) repressive efforts. The author’s suggestions are: First, the government needs to continuously socialize the dangers of the tendency of people to take the law into their own hands (eigenrichting) in cases of crime that occur. Second, the government should enforce the law firmly against people who take the law into their own hands (eigenrichting) without discrimination. Third, the government needs to improve the quality and quantity of the facilities and infrastructure it has